2015
DOI: 10.1113/jphysiol.2014.284430
|View full text |Cite
|
Sign up to set email alerts
|

Independent purinergic mechanisms of central and peripheral chemoreception in the rostral ventrolateral medulla

Abstract: The rostral ventrolateral medulla oblongata (RVLM) contains two functionally distinct types of neurons that control and orchestrate cardiovascular and respiratory responses to hypoxia and hypercapnia. One group is composed of the central chemoreceptor neurons of the retrotrapezoid nucleus, which provides a CO 2 /H + -dependent drive to breathe and serves as an integration centre and a point of convergence of chemosensory information from other central and peripheral sites, including the carotid bodies. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 66 publications
0
20
0
3
Order By: Relevance
“…Although transduction mechanisms remain undefined, a number of potential mechanisms may be excluded from con-sideration as contributors to the current results. For example, although pH/CO 2 sensitivity in the regions such as the retrotrapezoid nucleus is contributed to by astrocytes (Moreira et al 2015), glia are believed to play no role in raphe 5-HT neuron chemosensory transduction (Sobrinho et al 2014;Wu et al 2013). Similarly, despite the implication of acid-sensitive TASK channels in this process (Bayliss et al 2015;Putnam et al 2004), chemosensitivity of raphe 5-HT neurons does not appear to be dependent on TASK channels (Massey et al 2015;Wu et al 2008).…”
Section: Lmx1bmentioning
confidence: 99%
“…Although transduction mechanisms remain undefined, a number of potential mechanisms may be excluded from con-sideration as contributors to the current results. For example, although pH/CO 2 sensitivity in the regions such as the retrotrapezoid nucleus is contributed to by astrocytes (Moreira et al 2015), glia are believed to play no role in raphe 5-HT neuron chemosensory transduction (Sobrinho et al 2014;Wu et al 2013). Similarly, despite the implication of acid-sensitive TASK channels in this process (Bayliss et al 2015;Putnam et al 2004), chemosensitivity of raphe 5-HT neurons does not appear to be dependent on TASK channels (Massey et al 2015;Wu et al 2008).…”
Section: Lmx1bmentioning
confidence: 99%
“…; Moreira et al . ). Interestingly, Marina and collegues () showed that ATP release from astrocytes activates pre‐sympathetic brainstem neurones in the RVLM, thereby contributing to symphatoexcitacion, progression of ventricular remodelling and development of heart failure secondary to myocardial infarction (Marina et al .…”
Section: Introductionmentioning
confidence: 97%
“…The review by Moreira and colleagues entitled ‘Independent purinergic mecha‐nisms of central and peripheral chemoreception in the rostral ventrolateral medulla.’ describes the role of purinergic signalling at the level of the ventrolateral medulla in coordinating cardiorespiratory responses to hypoxia and hypercapnia by activating RTN chemoreceptors and presympathetic C1 neurons (Moreira et al . ). In the context of central chemoreception, evidence suggests that RTN astrocytes respond to high CO 2 by releasing ATP via connexin 26 hemichannels (Huckstepp et al .…”
mentioning
confidence: 97%